Un Organisme Sui GenerisÃ la Polynésie Français - Calinaud, René (Victoria University of Wellington Law Review, 2004)
The law of 5 February 1994 set up the Land Conciliation Commission of French Polynesia as a unique and original institution. Its creation was the result of considerable reflection on the treatment of land claims, which have their own particular characteristics and difficulties in this overseas territory. This article examines the success of the Commission, in light of its uncertain future after the creation of a land tribunal by the constitutional reform of 2004.